Strategi Pengembangan Ekowisata Kawah Balerang Masyarakat Kampung Paringgonan di Kabupaten Sipirok, Tapanuli selatan - Ahmad Rizki Harahap; Tri Martial; Saipul Batubara; Sularno Sularno; Ernita Ernita; Tengku hasan Basri (Owner : Riset dan Jurnal Akuntansi, 2023)
This research was conducted at Balerang Crater Ecotourism which is located in Situmba Julu Village, Sipirok District, South Tapanuli Regency. The purpose of this study (1) Describe the management of ecotourism in Balerang Crater. (2) Analyze the strengths, weaknesses, opportunities and threats (S.W.O.T) that exist in Balerang Crater ecotourism. (3) Formulate a strategy matrix for the development of Balerang Crater ecotourism. In this study the methods used were in-depth interviews, questionnaires, field observations, and also literature studies. Data analysis used qualitative analysis, quantitative analysis, and SWOT analysis (Strength, Weakness, Opportunity, & Threats). The results of this study explain that the management of Balerang Crater ecotourism requires community intervention, especially local communities in carrying out planning, development and management. Based on the SWOT analysis, it shows that alternative strategies that can be applied are in Quadrant III, namely the WO strategy. This strategy is a condition to minimize weaknesses in order to optimize existing opportunities. The development of the Balerang Crater Ecotourism area has considerable potential to contribute to potential economic opportunities that can have an impact on increasing people's income and as a whole will also increase regional original income (PAD). Ecotourism can be an economic potential that can be superior in accelerating rural economic growth, because the influence it gives has a broad impact on the environment of the community around the Balerang crater area. The opportunities for MSMEs around the ecotourism area will slowly grow following the development of ecotourism itself.